Pengaruh Akuntabilitas Laporan Keuangan Dana Desa dan Ketaatan Peraturan Perundang-undangan terhadap Kualitas Kinerja Bendahara Desa - Veronika Hutapea; Maftukhin; Hilda Kumala Wulandari; Roni; Anisa Sains Kharisma (Universitas Muhadi Setiabudi, 2019)
Compliance with laws and regulations is an important part that is directly related to the accountability of the performance of government agencies. This study aims to determine and analyze the effect of: accountability of village fund financial statements, compliance with laws and regulations, and accountability of village fund financial statements and compliance with laws and regulations on the quality of performance of village treasurers. The population in the study was 40 village treasurers. Sample selection uses a saturated sampling technique. The data used is primary data. Data collection in this study used questionnaires as research instruments. Test research instruments using validity and reliability tests. The hypothesis test uses a multiple regression test preceded by a normality test, a multicollinearity test and a heteroskedasticity test. Hypothesis testing using SPSS. The theoretical basis used is the theory of accountability of village fund financial statements, compliance with laws and regulations and the quality of performance of the village treasurer. The results showed that: the accountability of village fund financial statements partially has a significant effect on the quality of the village treasurer's performance, partial compliance with laws and regulations does not have a significant effect on the quality of the village treasurer's performance, the accountability of village fund financial statements and compliance with laws and regulations simultaneously have a significant effect on the quality of village treasurer's performance.